2001
DOI: 10.1002/1521-3889(200111)10:11/12<965::aid-andp965>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Wave phenomena in low-rate plastic flow of solids

Abstract: An investigation of plastic flow localization patterns (waves) which are ordered in space and evolve with time has been performed for a wide range of metals and alloys. These waves are found to have the following basic features: the dependence of propagation rate on work hardening coefficient, dispersion law and scale effect. The possibility of addressing plastic flow localization as a self‐organization process occurring in a deforming medium is considered. A set of equations appropriate for the description of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 20 publications
3
19
0
2
Order By: Relevance
“…Investigations performed in [35][36][37][38][39][40][41] showed that geometrically the localized plasticity pattern is the cross section of the volume autowave mode by the observable sample surface. To understand the nature of the phenomenon, it is important to compare the observable patterns with stages of work hardening [5,6] that can be seen on the flow curve σ(ε) or on the dependences θ(ε) [6,42].…”
Section: Patterns Autowaves Work Hardening Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations performed in [35][36][37][38][39][40][41] showed that geometrically the localized plasticity pattern is the cross section of the volume autowave mode by the observable sample surface. To understand the nature of the phenomenon, it is important to compare the observable patterns with stages of work hardening [5,6] that can be seen on the flow curve σ(ε) or on the dependences θ(ε) [6,42].…”
Section: Patterns Autowaves Work Hardening Stagesmentioning
confidence: 99%
“…The diagonal elements of the matrix coefficients of Equations (37) and (38) D εε D εσ D σε D σσ can be interpreted considering that the coefficient D εε is related to the mobile dislocation density and the coefficient D σσ is determined by the stress distribution. Then because of dimensionality reasons, it follows that D σσ ≈ F/ρ 0 (59) where F is the force of sample tension during testing and…”
Section: Spatial Scales Of the Plastic Flowmentioning
confidence: 99%
“…During recent decades we have focused on the macroscale development of plastic flow. The results are presented in papers [1][2][3] and in the monograph 4 . We have gradually come to accept that the plastic flow behavior has a characteristic attribute: the deforming medium would spontaneously separate into actively deforming layers alternating with inactive non-deformed layers (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…depends on the kind of material24 аnd ε* is the strain for the onset of linear work hardening stage. It follows from Eqs (1). and(40) that…”
mentioning
confidence: 99%
“…В наших исследованиях, обобщённых в статьях [1][2][3][4] и монографии [5], установлены главные макроскопические закономерности развития процесса пластического течения. Наиболее яркий атрибутивный признак её развития, обнаруженный с помощью адаптированной к этой проблеме методики двухэкспозиционной спекл-фотографии [5], состоит в самопроизвольной стратификации деформируемой среды на чередующиеся друг с другом активные и пассивные слои (рис.…”
Section: Introductionunclassified